Rancang Bangun Virtual Reality Tour Sebagai Inovasi Media Promosi Wisata Ecopark Berbasis Website - Chaerunisa, Adinda; Julianto, Indri Tri (Institut Teknologi Garut, 2025)
Garut is home to a number of pine forest ecoparks and natural attractions. These pine forests in Garut are known for their amazing natural attractions. Conventional media such as images, videos and texts have been used by natural attractions in Garut City as promotional media for disseminating information to tourists. However, this conventional media is less helpful because it only displays still images, videos and texts which are less interactive and real. Utilization of current technological advances such as Virtual Reality, can be applied to the media promotion of Ecopark natural attractions, especially pine forests as improving the experience of visitors before visiting tourist attractions so that visitors can consider appropriate transportation, distance, and road conditions to that location. The purpose of this research is to design a Virtual Reality Tour of Ecopark Nature Tourism that can be used as a suggestion of places to visit and provide information to prospective visitors. The method used in this research is the Multimedia Development Life Cycle with six stages, namely concept, design, material collection, manufacture, testing and distribution. The testing technique in this research is alpha testing using black box. The final results of this study obtained the Ecopark Virtual Reality Tour Website with chat bot features, Maps, hotspots, audio narration and backsound.